Cakra: A Counseling Application Based on Catur Paramita in Building Resilience - Putu Ari Dharmayanti; Luh Putu Sri Lestari; Kade Sathya Gita Rismawan (Jurnal Pedagogi dan Pembelajaran, 2025)
Elementary school students face emotional challenges that have not been optimally addressed through existing counseling media. This study aims to develop a digital counseling application called Cakra, based on the values of Catur Paramita, to build the resilience of elementary school students. The method used is Research and Development (R&D) with a limited development model from Borg & Gall up to the initial product design stage. The research subjects consisted of six experts (two media experts, two content experts, and two language experts) and ten trial subjects (one teacher, three individual test students, and six small group test students). Data collection techniques included observation, interviews, and questionnaires. The validation results showed that the CAKRA application received highly valid scores from the language experts (96%), content experts (95.5%), and media experts (96.5%). The practicality test also indicated a very practical level, with scores of 96% in individual tests, 95% in small group tests, and 90% from the teacher. These findings indicate that CAKRA is feasible to use as a supporting medium for counseling services to enhance students' mental resilience. The implications of this study highlight the potential of the CAKRA application as a culturally based innovation in character education and children's emotional well-being. Further research is recommended for long-term testing and the development of application features based on user needs.